Digital Emotional Capital: Social Media Interactions and Their Impact on the Construction of Prestige and Social Exclusion - James Josmell Ojeda Portugal; Juana Francisca Pillco Delgado; Luis Felipe Ticona Lecaros; Ruth Martha Frisancho De Martinez; Luis Alonzo Contreras Chavez (Universidad Ciencia y Tecnología, 2026)
The objective of this study was to analyze the relationship between academic stress and emotional regulation in university students exposed to high-demand academic environments. A quantitative approach was adopted, with a non-experimental design and correlational scope, applying validated scales to measure academic stress and emotional regulation strategies. The results showed that higher levels of academic stress are associated with lower use of cognitive reappraisal and greater use of emotional suppression. These findings suggest that high academic demands promote more reactive emotional regulation styles, which may increase psychological strain. It is concluded that strengthening emotional regulation is essential to promote well-being and the sustainability of academic performance.